The Effectiveness of Comprehension of Da'wah Texts in the Frame of Hans-Georg Gadamer - Enung Asmaya,; Sholihah, Amirotun (Proceeding of Dakwah Saizu International Conference, 2023)
The effectiveness of understanding in receiving da'wah texts is a priority. The level of understanding of da'wah texts is one of the priorities in da'wah. The ability to understand da'wah texts can be seen from the desire to externalize da'wah texts in everyday life. In fact, he uses a different point of view on a text that is more contextual. An active and dynamic attitude in understanding da'wah texts shows that understanding of the Gadamaer pattern has been achieved. Study This aim in describing and studying Gadamer's framework in achieving the effectiveness of understanding da'wah texts. This study used a qualitative approach with literature analysis techniques. The analysis comes using the frame of Gadamer's method in the form of fusion of horizons, awareness influence history , circle hermeneutics and applications . Research Results show that Gadamer gave direction to mad'u in the process of understanding not to “stupid”, and to be passive. But an attitude that is active, dynamic, creative and innovative. There is a wise attitude towards the text to accept the text without any prejudice, to be open to accept what the text is, with the understanding that every text has its historicality. According to Gadamer, Mad'u has pre-understanding before understanding so that in the process it finds new contextual meanings. Can find the outside normal from What exists text